Occupational social class, risk factors and cardiovascular disease incidence in men and women: a prospective study in the European Prospective Investigation of Cancer and Nutrition in Norfolk (EPIC-Norfolk) cohort. - McFadden, E; Luben, R; Wareham, N; Bingham, S; Khaw, K (2008)
OBJECTIVES: To investigate the association between occupational social class and cardiovascular disease (CVD) incidence, and the extent to which classical and lifestyle risk factors explain such relationships, and if any differences persist after 65 years of age. DESIGN, SETTING AND PARTICIPANTS: Prospective population study of 22,478 men and women aged 39-79 years living in the general community in Norfolk, United Kingdom, recruited using general practice age-sex registers in 1993-1997 and followed up for total mortality to 2006. MAIN RESULTS: In both men and women an inverse relationship was observed between social class and CVD incidence, with a relative risk of social class V compared to I of 1.90 in men (95% CI 1.47 to 2.47, P < 0.001) and 1.90 in women (95% CI 1.45 to 2.49, P < 0.001). Adjusting for classical and lifestyle risk factors (age, smoking, BMI, systolic blood pressure, total blood cholesterol, history of diabetes, physical activity, weekly alcohol intake and plasma vitamin C levels) had little effect in men; the relative risk of social class V compared to I of 1.70 (95% CI 1.31 to 2.22, P < 0.001), while there was some attenuation seen in women, relative risk of social class V compared to I of 1.56 (95% CI 1.18 to 2.05, P = 0.011). The association persisted in men and women aged > or =65 years. CONCLUSIONS: Some but not all of the socioeconomic differential in CVD incidence can be explained by potentially modifiable classical and lifestyle risk factors. Low social class remains a risk factor for CVD after age 65 years. Further understanding of the mechanisms underlying the association is needed if we are to reduce inequalities in health.